E-sport related intrinsic and extrinsic motivation in practice. Initial psychometric properties of the "E-sport and ME" questionnaire - Krzysztof Horoszkiewicz; Grzegorz Załęski; Bartosz Horoszkiewicz (Kazimierz Wielki University, 2022)
Background. The popularity of eSports is rapidly increasing, and PC gamers are watched by crowds of spectators similarly to traditional sports. The aim. E-Sport and ME questionnaire was created to assess motivation for playing video games and competing in tournaments. Material and methods. The theoretical background was grounded in self-determination theory (SDT). The results of 203 men aged 14 to 33 years (M = 20.4; SD = 3.4) were studied. Exploratory and confirmatory factor analyses (EFA and CFA) were conducted. Results. Both EFA and CFA indicated two solid factors: extrinsic and intrinsic motivation [Comparative Fit Index = 0.995, Tucker Lewis Index = 0.994, Root Mean Square Error of Approximation = 0.046 (CI 0.00 - 0.08), Standardized Root Mean Square Residual = 0.075 (χ2 = 64.16, df = 53)]. Both scales had a high level of internal consistency (> α = 0.8). Respondents from professional e-sports clubs have higher extrinsic motivation than amateurs; intrinsic motivation takes place on similar level.  Conclusions. The statistical analysis of e-sport and myself revealed a high level of internal consistency as well as the identification of two distinct factors. This could aid coaches and players in outlining the dominant type of motivation for playing video games. The shown version should be further explored and validated to increase its generalizability.